2021
DOI: 10.1186/s12902-021-00789-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between PNPLA3 rs738409 polymorphism and nonalcoholic fatty liver disease: a systematic review and meta-analysis

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) is a common disorder that is known to be the leading cause of chronic liver disease worldwide. This study aims to systematically review and meta-analyze the association between PNPLA3 rs738409 polymorphism and non-alcoholic fatty liver. Methods Following a systematic review and meta-analysis method, articles without any time limitation, were extracted from SID, MagIran, IranDoc, Scopus, Embase, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 51 publications
0
26
0
2
Order By: Relevance
“…Further GWAS studies have replicated the correlation of rs738409 C>G p.I148M with steatosis, fibrosis and NAFLD disease severity [ 212 , 213 , 214 ]. A recent meta-analysis suggested that patients with GG genotype are 105% more likely to develop NAFLD than patients who had other genotypes (OR 2.5, 95% CI, 1.64–2.56) [ 215 ]. Rs738409 is now considered an established genetic biomarker for NAFLD, with G-allele carriers also being at risk of liver failure and liver-related fibrosis mortality, as well as developing hepatocellular carcinoma [ 216 ].…”
Section: Omics-related Diagnostic Research Technologiesmentioning
confidence: 99%
“…Further GWAS studies have replicated the correlation of rs738409 C>G p.I148M with steatosis, fibrosis and NAFLD disease severity [ 212 , 213 , 214 ]. A recent meta-analysis suggested that patients with GG genotype are 105% more likely to develop NAFLD than patients who had other genotypes (OR 2.5, 95% CI, 1.64–2.56) [ 215 ]. Rs738409 is now considered an established genetic biomarker for NAFLD, with G-allele carriers also being at risk of liver failure and liver-related fibrosis mortality, as well as developing hepatocellular carcinoma [ 216 ].…”
Section: Omics-related Diagnostic Research Technologiesmentioning
confidence: 99%
“…The variants are correlated with the release of pro-inflammatory and pro-fibrogenic cytokines such as chemokine ligand 5, monocyte chemoattractant protein-1, IL-8, granulocyte-macrophage colony-stimulating factor, and TNF-α [81] . Individuals harbouring the rs738409 variant had greater inflammatory infiltration than individuals with wild- type genotypes [ 84 ] . Accordingly, the culture medium of cells expressing the genetic variants was also shown to recruit more immune cells than the wild-type carriers [ 81 ] .…”
Section: Resultsmentioning
confidence: 99%
“…Patatin-like phospholipase domain-containing protein 3 ( PNPLA3 ) is a lipid droplet-associated protein that hydrolases triglycerides and retinyl esters [ 100 ] in adipocytes and hepatocytes, in which it helps regulate both lipogenesis and lipolysis [ 101 , 102 ]. The expression of the PNPLA3 gene decreases during fasting and increases after eating, suggesting a role for PNPLA3 protein in processing and storing fats in the diet [ 103 ].…”
Section: Genetic Susceptibility To Nafldmentioning
confidence: 99%